Giant peroxisomes in a moss (Physcomitrella patens) peroxisomal biogenesis factor 11 mutant. Issue 2 (6th November 2015) - Kamisugi, Yasuko; Mitsuya, Shiro; El‐Shami, Mahmoud; Knight, Celia D.; Cuming, Andrew C.; Baker, Alison
Summary: Peroxisomal biogenesis factor 11 (PEX11) proteins are found in yeasts, mammals and plants, and play a role in peroxisome morphology and regulation of peroxisome division. The moss Physcomitrella patens has six PEX11 isoforms which fall into two subfamilies, similar to those found in monocots and dicots. We carried out targeted gene disruption of the Phypa_PEX11‐1 gene and compared the morphological and cellular phenotypes of the wild‐type and mutant strains. The mutant grew more slowly and the development of gametophores was retarded. Mutant chloronemal filaments contained large cellular structures which excluded all other cellular organelles. Expression of fluorescent reporter proteins revealed that the mutant strain had greatly enlarged peroxisomes up to 10 μm in diameter. Expression of a vacuolar membrane marker confirmed that the enlarged structures were not vacuoles, or peroxisomes sequestered within vacuoles as a result of pexophagy. Phypa_PEX11 targeted to peroxisome membranes could rescue the knock out phenotype and interacted with Fission1 on the peroxisome membrane. Moss PEX11 functions in peroxisome division similar to PEX11 in other organisms but the mutant phenotype is more extreme and environmentally determined, making P. patens a powerful system in which to address mechanisms of peroxisome proliferation and division.